Graphene oxide derived from biomass and their potential photocatalytic application - M. S., Amir Faiz; C.A., Che Azurahanim (Bridge Center, 2019)
Recently, abundance of research reported the works related to waste to wealth (WTW) concept. There has been a lot of research done using sources from animal and plant to mimick the synthesis of carbonaceous materials from natural resources. Graphene, the world exciting material also was included in WTW concept where researchers trying to produce from biomass and waste. Graphene oxide (GO), which is in the family of carbon materials is extensively research for their various applications including photocatalyst. Hence, this review focuses on synthesis of GO from biomass, the synthesis of nanocomposites and the photocatalytic activity of GO based nanocomposites.